OM FAGLIG-PÆDAGOGISK FORSKNING, DENS GENSTAND OG DENS METODOLOGI - Jensen, Jørgen Aage (Psyke & Logos, 2022)
The thesis is advanced that a mature science is characterised by accumulation of knowledge, an immature science by a replacing, or superseding of points of view and their associated observations. The ambition is to make a contribution to the discussion of the conditions for making research in science curricula a mature scientific endeavour. On the basis of an outline of important features of the scientific endeavour, including an attempt at characterising the concept of scientific observation, a description of the object of science curricular research is offered, as well as a frame for its research. In the present article this frame is established as a heuristic for assumptions about and observations of human acquisition processes. Some examples of possible research topics for science curricular research in agreement with the heuristic are briefly presented.